2021
DOI: 10.3389/fphys.2021.656455
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as Potential Mediators for Exercise-Induced Positive Effects on Neuroplasticity and Cerebrovascular Plasticity

Abstract: The accumulated evidence from animal and human studies supports that exercise is beneficial to physical health. Exercise can upregulate various neurotrophic factors, activate neuroplasticity, and play a positive role in improving and enhancing cerebrovascular function. Due to its economy, convenience, and ability to prevent or ameliorate various aging-related diseases, exercise, a healthy lifestyle, is increasingly popularized by people. However, the mechanism by which exercise performs this function and how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 136 publications
(184 reference statements)
1
11
0
Order By: Relevance
“…It is in accordance with previous studies showing an increase in cortical lactate concentrations after an acute endurance exercise on treadmill in healthy rats (Takimoto and Hamada 2014;Coxon et al 2018). Other studies reported a direct influence of lactate originated from active skeletal muscles, on neurotrophic/angiogenic activity and on long-term potentiation that constitutes the basis of learning and memory (Suzuki et al 2011;Morland et al 2017;El Hayek et al 2019;Huang et al 2021). Finally, HIIT also upregulates cortical COX 4 levels, concomitantly with endurance improvements at 2 and 8 weeks.…”
Section: Levels Of Neuroplasticity Markers Are Time-dependent Over Th...supporting
confidence: 91%
“…It is in accordance with previous studies showing an increase in cortical lactate concentrations after an acute endurance exercise on treadmill in healthy rats (Takimoto and Hamada 2014;Coxon et al 2018). Other studies reported a direct influence of lactate originated from active skeletal muscles, on neurotrophic/angiogenic activity and on long-term potentiation that constitutes the basis of learning and memory (Suzuki et al 2011;Morland et al 2017;El Hayek et al 2019;Huang et al 2021). Finally, HIIT also upregulates cortical COX 4 levels, concomitantly with endurance improvements at 2 and 8 weeks.…”
Section: Levels Of Neuroplasticity Markers Are Time-dependent Over Th...supporting
confidence: 91%
“…Our work demonstrated the modulation of a cortico-amygdala neural circuit by exercise training in improving stress resilience. Currently available explanations for physical exercise and mental health mainly explored the regulation of brain homeostasis such as neuroinflammation 10 , 24 , cerebrovascular function 25 , 26 or oxidative stress 9 , 27 . These changes in brain microenvironment further contribute to the acceleration of adult neurogenesis, leading to the improvement of mental 8 , 28 or cognitive functions 7 , 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This anabolic molecule reaches the brain to induce BDNF production (Herold et al, 2019;Pinho et al, 2019). Additionally, the lactate generated during exercise is another potential molecule to enhance the synthesis of BDNF in brain; consequently, increasing the BDNF concentration in the periphery (Hashimoto et al, 2021;Huang et al, 2021). In this sense, resistance training in older people is a stimulus that increase blood lactate in healthy elderly (Valkeinen et al, 2006;Simões et al, 2013).…”
Section: Discussionmentioning
confidence: 99%